Intra-tumoral NK cells and their association with patient outcomes: a novel prognostic model incorporating NK cells and clinicopathologic features in gastric cancer - Oshi, Masanori; Tamura, Yuko; Wu, Rongrong; Rog, Colin J.; Yan, Li; Yuza, Kizuki; Kosaka, Takashi; Akiyama, Hirotoshi; Ishikawa, Takashi; Takabe, Kazuaki; Endo, Itaru (Frontiers in Immunology, 2026)
BackgroundNatural killer (NK) cell infiltration has been implicated in the prognosis of gastric cancer patients. However, NK cell infiltration fraction has not yet been used routinely in clinical practice due to a lack of a measure for accurate quantification.MethodsNK cell infiltration fraction was quantified using a deconvolution tool and its clinical relevance was investigated in gastric cancer patients from our institution (Yokohama City University Hospital (YCU) and those present in publicly available cohorts with transcriptome data (TCGA, GSE84437 and GSE150290).ResultsIn the single cell sequencing cohort, the distribution of NK cells was similar to that of NK cell-related gene expression. High NK cell infiltration in gastric cancer correlated with enriched immune gene sets, such as IFN-α and IFN-γ responses, and also linked to increased cytolytic activity and low stromal cell infiltration along with higher mutation rates. Clinically, high NK cell infiltration was associated with better overall survival and improved response to neoadjuvant chemotherapy. Additionally, combining NK cell score with clinicopathological factors, including age at a diagnosis and AJCC T- and N-category, provided a powerful prognostic score for gastric cancer patients which was found to be consistent in multiple cohorts.ConclusionsGastric cancer with high NK cell infiltration is associated with increased immune activity and lower stromal cell infiltration, potentially impacting patient prognosis. Combining clinicopathological factors with NK cell score provides a powerful tool for prognostication of gastric cancer patients.